Cross-hybridization on PCR-spotted microarrays. - Wren, J.D (IEEE Engineering in medicine and biology magazine)
While more work is certainly necessary to better quantify the effects of hybridization stringency conditions on PCR-spotted microarrays, we find that sequence similarity requirements for observing cross-hybridization on these microarrays are slightly higher than, yet similar to, those observed for oligonucleotide arrays. These results suggest that consideration needs to be given to probe design for genes containing repetitive regions, as cross-hybridization can impact expression studies in two ways: 1) unrelated genes can appear to co-vary by virtue of a cross-hybridizing region; and 2) true expression variations of a gene could be masked by the cross-hybridizing signal of another gene. Both issues become even more of a concern when dealing with transcripts expressed at low levels because a small amount of overlap from an up-regulated gene would provide enough false signal to make covariance seem significant.